Investigation on Prevalence of Canine Trypanosomiasis in the Conservation Areas of Bwindi-Mgahinga and Queen Elizabeth in Western Uganda - James Robert Ochieng; Marta Planellas Bachs; Anthony Nsubuga; Innocent B. Rwego; John Joseph M. Kisakye; Laura Muro Riba; Jesus Muro Figueres (Journal of Parasitology Research)
Nowadays, despite the instauration of several control strategies, animal trypanosomiasis continues to be reported all over Uganda. Few canine African trypanosomiasis (CAT) studies have been carried out, yet dogs are known Trypanosoma reservoirs that share identical home ranges with livestock and serve as parasite link between livestock and humans. This study evaluates the prevalence of CAT in dogs in the Bwindi-Mgahinga and Queen Elizabeth conservation areas. This information will be useful to evaluate the possible role of dogs in the transmission cycle of Trypanosoma species in livestock and wild animals. Trypanosome tests using microhematocrit centrifugation/dark ground microscopy technique (MHCT) followed by conventional polymerase chain reaction (cPCR) were performed in blood samples collected from identified indigenous dogs (n=124). Four (3.23%) out of 124 dogs were positive for CAT. One dog was positive with Trypanosoma congolense and three with T. vivax. There was no significant statistical difference in CAT prevalence rate in relation to dog’s age, sex, and site (P>0.05). This study reports what we believe is the first time detection of T. congolense and T. vivax in the indigenous dogs found in the Bwindi-Mgahinga and Queen Elizabeth conservation areas in western Uganda. The noticed T. congolense and T. vivax could be responsible for both canine and animal trypanosomiasis and represent a serious threat to the livestock industry. Therefore, there is a need for continuous trypanosomiasis surveillance and integrated management in contiguity to wildlife reserves.